A thermal behaviour study of solid-state cinnamates of the latter trivalent lanthanides and yttrium(III) - Carvalho Filho, M. A. S.; Fernandes, N. S. [UNESP]; Fertonani, F. L. [UNESP]; Ionashiro, Massao [UNESP] (Elsevier, 2003)
Some new compounds of cinnamic acid with the latter trivalent lanthanides and yttrium(III) were synthesized in the solid state. The compounds have the general formula LnL3, where Ln represents trivalent Eu to Lu or Y ions and L is the cinnamate anion (C6H5-CH=CH-COO-). Thermogravimetry (TG), derivative thermogravimetry (DTG), differential scanning calorimetry (DSC), infrared absorption spectra and X-ray diffraction powder patterns were used to characterize and to study the thermal behaviour of these compounds. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Cinnamate; Latter lanthanides and yttrium; Thermal behaviour; cinnamic acid; lanthanide; yttrium; absorption spectroscopy; chemical analysis; differential scanning calorimetry; infrared spectroscopy; solid state; thermal analysis; thermogravimetry; X ray diffraction